Upaya Meningkatkan Kemampuan Mengenal Angka 1 sampai 10 melalui Permainan Kartu Angka pada Anak Usia Dini - Dias Syafitri Nurinta; Yasniwarti Yasniwarti; Zaenal Muftie (Jurnal Pendidikan Raudhatul Athfal, 2018)
This study aims to improve the ability to recognize numbers 1 to 10 in children group A RA Nurul Amal Ciguruwik in Cileunyi District, Bandung Regency through a number card game. This research is a classroom action research conducted collaboratively between researchers and teachers. The subjects in this study were 13 children of A RA Nurul Amal Group consisting of 7 girls and 6 boys. Data collection techniques are carried out using observation, performance, and documentation. Data analysis techniques were carried out descriptively qualitative and quantitative. the results of the study showed that increasing the ability of children to know numbers 1 to 10 before using a number card game had an average score of 50.64. Teacher activity in the first cycle showed a percentage of 76.47% then in the second cycle increased to 97.06%. Children's activity in cycle I was 72.65% increasing to 95.3% in cycle II. The average value of the ability to recognize numbers 1 to 10 in the first cycle of 64.74 turned out to have increased in the second cycle of 78.85. So increasing the ability to recognize numbers before and after recognizing numbers 1 to 10 is 28.21.